Toponimi Penamaan Jalan di Kota Surabaya - Risma Putri Anggraini (sarasvati, 2023)
ABSTRACTThis research is motivated by the different variations of street names in Surabaya. Names are not only given to living things as a person's personal identity, but are also used as regional identity markers. Street names in Surabaya itself vary widely, some of which refer to names of plants, animals, and others. The naming of roads in Surabaya is inseparable from the cultural context and local natural features. Based on these. This study aims to describe the categorization of street names in the city of Surabaya. This research is a qualitative descriptive study. The data collection technique used is documentation as supporting evidence for the results of a data. The results of the data analysis obtained from the toponomi of street names in Surabaya are categorized into several aspects including embodiment aspects, social aspects and cultural aspects. As for the naming of roads based on embodiment aspects, namely, the form of water, flora, fauna, topographical forms, elements of natural objects, elements of location. Both street names are based on social aspects, including activities, names of figures and praise. Finally, the naming of roads based on cultural aspects of the struggle for independence, kingdoms, community events and beliefs.Keyword: toponymy, street naming, Surabaya City.